THE EFFECTS OF ELECTROMAGNETIC TREATMENTS ON THE GROWTH AND PALMITIC ACID CONTENT OF Cynara cardunculus - Mahmoud A. Sharaf-Eldin (Journal of Animal and Plant Sciences, 2016)
A field experiment on cardoon seeds (Cynara cardunculus L.) was carried out during two successive seasons to study the effect of electromagnetic fields (EMF) on cardoon growth and its palmitic acid content. A 75 mT (millitesla) EMF was used as follows: EMF0 (control) not exposed to the magnetic field, three different EMF exposure durations studied as EMF1 (T1): 15 min, EMF2 (T2): 30 min, or EMF3 (T3): 45 min, considered for both non-soaked/dry (D) and soaked seeds (W). The EMF had significant effects on most of the studied parameters. EMF2D and EMF3W exhibited the best growth attributes for dry and soaked seeds, respectively. Additionally, the palmitic acid (C16:0) content in producing seeds was significantly influenced by 15 and 30 min of exposure to the EMF, in the case of dry seeds. The maximum value of palmitic acid content was 11.83% compared to a control value of 9.30%. These findings suggest that EMF treatments of cardoon seeds have the potential to enhance the cardoon plant growth and the palmitic acid content.
Keywords: cardoon; Cynara cardunculus; electromagnetic field; palmitic acid; seed